Banking Product Marketing Strategy through Instagram Social Media in the Middle of the Covid-19 Pandemic - I Kadek Arya Wibawa; Agus Fredy Maradona (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
The banking industry, especially BPR, has been affected by the COVID-19 pandemic. BPR Lestari wrote in a release that their assets grew in the midst of a pandemic. It is known that this bank is quite active in using social media even before the COVID-19 pandemic emerged. The purpose of this study was to find out how to implement changes in marketing strategies from conventional to marketing strategies through social media, especially Instagram in the midst of the COVID-19 pandemic. In this study, the sampling technique used was purposive sampling. Using data analysis techniques carried out in four steps, namely data collection, data reduction, data presentation and drawing conclusions/verification. The research validity test is the source triangulation test. The result of this study reveals that BPR Lestari has made maximum use of social media Instagram in supporting its marketing process in the midst of this COVID19 pandemic. Instagram BPR Lestari can fulfill every stage of the 5A concept (Aware, appeal, ask, act, and advocate) Marketing 4.0. Where the indicator for the success of marketing 4.0, namely at the advocate stage, has been achieved by BPR Lestari, as evidenced by the recommendations made either directly or through the Instagram share feature voluntarily by the customers of this bank. It can be concluded that the role of Instagram social media and digital marketing transformation has made BPR Lestari survive in the midst of the pandemic and even experience an increase in its assets.